EVALUASI TINGKAT USABILITAS WEB MOBILE PERGURUAN TINGGI NEGERI MENGGUNAKAN METODE USABILITY TESTING - Fadliyani Nawir; Alzeda Wira (JNSTA ADPERTISI JOURNAL, 2021)
Pademi Covid 19 has brought big changes to community activities. Digitalization is seen in various aspects, both industry, government and private institutions. The impact of this pandemic has also caused several industrial sectors to lay off their employees. Bank Indonesia released the industrial sector affected by Covid 19, including the education sector. The PSBB, which is implemented by the government, makes educational activities carried out from home, the learning process is carried out through digital media, not only that the registration process for prospective students and students is also carried out through digital media. Thanks to the Covid 19 Pandemic, internet users via mobile devices have also increased very rapidly. User experience in interacting with the web is something that must be considered by web designers and developers to provide convenience. Usability is a theory used to measure the quality of user interaction with an information system based on both web and mobile applications. From the results of this study, it can be concluded that the level of usability of the college mobile web can be concluded that the responsive design used as a mobile method by the college web has a high level of usability through the aspects of designing for a goal, layout, visual and interaction design and navigation.